The associations between lumbar proprioception and postural control during and after calf vibration in people with and without chronic low back pain - Hao, Zengming; Cheng, Xue; Jiang, Haimei; Yang, Jiajia; Li, Yan; Ambrose Lo, Wai Leung; Yu, Qiuhua; Wang, Chuhuai (Frontiers in Bioengineering and Biotechnology, 2024)
The relationships of lumbar proprioception with postural control have not been clarified in people with chronic low back pain. This study aimed to compare the associations between lumbar proprioception and postural control in response to calf vibration in individuals with and without chronic low back pain. In this study, we recruited twenty patients with chronic low back pain (CLBP group) and twenty healthy control subjects (HC group) aged between 18 and 50 years. The passive joint reposition sense (PJRS) test for two positions (15° and 35°) were used to assess lumbar proprioception and expressed as the mean of reposition error (RE). Postural control was tested by adding and removing calf vibration while standing on a stable force plate with eyes closed. The sway velocity in the anterior-posterior (AP) direction of center of pressure (COP) data with a window of 15s epoch at baseline, during and after calf vibration was used to evaluate postural control. The major results are: (1) significantly higher PJRS on RE of 15° and 35° were found in the CLBP group; (2) AP velocity was not different between two groups at baseline and during calf vibration. However, AP velocity was significantly larger in the CLBP group compared with the HC group at epoch 2-14 after calf vibration, and AP velocity for the CLBP group took a longer time (23 epochs) to return to the baseline after calf vibration compared with the HC group (9 epochs); (3) lumbar proprioception represented by PJRS on RE of 15°correlated negatively with AP velocity during vibration for the HC group. Within the CLBP group, no significant relationships between PJRS on RE for two positions (15° and 35°) and AP velocity in any postural phases were found. In conclusion, the CLBP group has poorer lumbar proprioception, slower proprioceptive reweighting and impaired postural control after calf vibration compared to the HC group. Lumbar proprioception offers different information on the control strategy of standing control for individuals with and without CLBP in the situations with proprioceptive disturbance. These results highlight the significance of assessing lumbar proprioception and postural control in CLBP patients.